2016
DOI: 10.1080/03079457.2016.1143086
|View full text |Cite
|
Sign up to set email alerts
|

Variability of tropism and replicative capacity of two naturally occurring influenza A H9N2 viruses in cell cultures from different tissues

Abstract: Studies carried out on cell permissivity are of great interest to understand virus replication and pathogenicity. We described the results of a comparative analysis of replication efficiency of two naturally occurring influenza A H9N2 variants isolated from poultry and wild birds, differing by only two substitutions Q226L and T384N, in the receptor-binding site of haemagglutinin and the 380 loop region of NA proteins, respectively. Considering the overall growth of both viruses, lung cultures ensured the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…H9N2 viruses have emerged in Tunisia in 2009 causing several outbreaks in poultry flocks [119]. AIV H9N2 virus was also isolated from wild birds [120]. Moreover, a nationwide serosurvey of 800 flocks in 2010-2011 indicated widespread AIV infection including H9N2.…”
Section: Tunisiamentioning
confidence: 99%
“…H9N2 viruses have emerged in Tunisia in 2009 causing several outbreaks in poultry flocks [119]. AIV H9N2 virus was also isolated from wild birds [120]. Moreover, a nationwide serosurvey of 800 flocks in 2010-2011 indicated widespread AIV infection including H9N2.…”
Section: Tunisiamentioning
confidence: 99%
“…Viruses used in this study replicated in different cultured cells without trypsin, although cells were infected with low multiplicity and extracellular virions were removed by treatment of cells with citrate buffered saline and washing with PBS. The efficient replication of some H9N2 viruses in primary chicken cells without exogenous trypsin has been previously reported 43 . Our results showed that TMPRSS2 and to a lesser extent HAT can support multiple-cycle replication of different viruses, particularly G319, better than trypsin.…”
Section: Discussionmentioning
confidence: 86%
“…LPAIV tropism in avians is classically restricted to the respiratory and enteric tracts due to the localisation of trypsin as the protease required for HA CS activation during infection 47 . However, chicken H9N2 in vitro studies have shown that other proteases may activate the LPAIV CS 61 , 62 , and in some circumstances include the ubiquitous furin protease, normally associated with HPAIV CS activation 63 . While there are no reported descriptions of alternative proteases in turkey tissues, it is speculated that non-trypsin proteases may have facilitated H7N9 LPAIV CS activation in multiple visceral organs.…”
Section: Discussionmentioning
confidence: 99%